PENGEMBANGAN ALAT UKUR SKALA SELF REGULATED LEARNING PADA MAHASISWA YANG MENGALAMI BURNOUT AKADEMIK - Sofa, Puput Nurbani; Andini, Dea Raisa Andini; Dya, Dhea Aprilina; Luthfiah, Khoirunnisa; Fathiarafa, Maritza; Aditiya, Yoga; Ramdani, Zulmi (Yayasan Indonesia Bermutu, 2024)
Self-regulation is a process whereby a person can manage the achievement of their actions, evaluate their success when achieving the target. The purpose of this research is to develop a valid and reliable measurement tool to determine the level of self-regulation in students. There are 41 items given to 459 active students who ever felt physically and emotionally exhausted during college. The method used in this research is quantitative method and reading literature. The sample in this study was obtained using a non-probably sampling method with a purposive sampling technique. The results of this study obtained 16 items which became the final items with the Likert scaling model, supplemented by SPSS analysis. The self-regulated learning scale shows quite good validity 0,829, 0,712, dan 0,787 and reliability values 0.879. So that we get the development of measuring tools that are quite valid and reliable in measuring self-regulated learning in students.